Avoiding the Value Added Tax Theory and Cross-Country Evidence - de Mello, Luiz (OECD Economics Department Working Papers, 2008)
This paper develops a differential game of tax avoidance by modelling the interactions between a taxpayer and the tax authority. This framework is particularly useful for explicitly modelling situations of conflict. The solution to the game is a non-co-operative Nash that depends on the resources that need to be used by the tax authority to enforce legislation and the cost to be borne by the taxpayer in tax compliance, provided that the curvature of the utility functions is bounded. Empirical evidence is provided for the value added tax (VAT) using a cross-section of OECD and non-OECD countries. OECD indicators of tax administration efficiency are included in the regressions. The empirical findings show that VAT efficiency, defined as the ratio of collections as a share of consumption to the statutory rate, rises the lower the VAT rate, the lower the share of administrative costs in tax revenue (proxying for the efficiency of tax administration), the more pro-competition the regulatory framework in product markets (measuring non-tax incentives for non-compliance) and the better the country's governance indicators (regulatory quality, rule of law and government effectiveness). This paper is forthcoming in the Public Finance Review